Evaluación tomográfica del mixoma odontogénico en maxilar superior. Reporte de caso y revisión de la literatura - Tenorio-Estrada, Janet Kely (2024)
Odontogenic myxoma (OM) is a slow-growing, painless, aggressive and non-metastatic central jaw tumor of mesenchymal origin. Radiographically, it can vary from a unilocular radiolucent lesion to a multilocular lesion with well-defined or diffuse margins. The aim of this paper is to recognize the radiographic and tomographic characteristics of OM in a patient who attended the Dental Clinic of the Faculty of Dentistry of the Universidad Nacional Mayor de San Marcos in Lima-Peru. Case presentation: 86 year old male patient, who in the panoramic radiography indicated for his oral rehabilitation, a unilocular radiolucent image was found in the anterosuperior area with partially defined limits, corticalized edges and oval shape. In the volumetric tomography there was evidence of thinning and erosion of both bone tables, thinning of the floor of the nasal cavity. The radiolucent image seems to havean extension close to the alveolar ridge. In adition, there was an effacement of the cortices of the nasopalatine duct. The lesion was enucleated and an anatomopathological examination was performed. Diagnosis was odontogenic myxoma. The patient was evaluated at one year and six months with satisfactory results. The wide variety of radiographic characteristics of odontogenic myxoma leads us to think of a large number of differential diagnoses, being the histological evaluation together with the imaging analysis the ones that provide a definitive diagnosis. Although the anterosuperior area is the least common for its presentation, radiolucent images in this area should be considered as possible odontogenic myxomas, since this condition is more frequent in latín race.